Statistically Optimized Nano Emulsion Enhances Bone Regeneration Efficiency of Ipriflavone in Osteoporosis-Induced Zebrafish Model - John, Anish; Subramanyabhat, Sreehari Malangai; Mohan, Masmarika; Vadakkepushpakath, Anoop Narayanan; Chakraborty, Gunimala; Mahadev, Manohar (Indian Journal of Pharmaceutical Education and Research, 2025)
Background The objective of this research was to develop a nano emulsion of ipriflavone (IP nano emulsion), a soy isoflavone to enhance its solubility, bioavailability and bone regeneration potential. Materials and Methods The oil phase and surfactants for the IP nano emulsion were selected by plotting ternary phase diagrams. Optimisation of surfactant and oil concentrations was achieved using the Box-Behnken Design in Design Expert software. A monodisperse nano emulsion was produced using sonication and the globule size was below 100 nm. The zeta potential readings for the below -15 mV. The optimised formulation was tested for its morphology and examined using TEM imaging. Results In vitro drug release studies exhibited a release of 80% of ipriflavone in 90 min. The selected formulation demonstrated stability over a three-month period in accelerated conditions of temperature and humidity. The bone regeneration capacity of IP nano emulsion was tested on a dexamethasone-induced osteoporotic zebrafish model. The Caudal vertebrae bone of treated zebrafish showed significant bone regeneration compared to untreated and was confirmed by length measurements. Conclusion The nano emulsion displayed effective bone regeneration capability in zebrafish models, indicating the usefulness of nano emulsion in the treatment of osteoporosis.
Keywords: Ipriflavone; Nano emulsion; Osteoporosis; Zebrafish model; Bone regeneration